2016
DOI: 10.1063/1.4959211
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-solutal capillary-buoyancy flow of a low Prandtl number binary mixture with a −1 capillary ratio in an annular pool

Abstract: A series of three-dimensional numerical simulations on thermal-solutal capillary-buoyancy flow in an annular pool were carried out. The pool was filled with silicon-germanium melt with an initial silicon mass fraction of 1.99%. The Prandtl number and the Lewis number of the working fluid are 6.37 × 10−3 and 2197.8, respectively. Both the radial temperature gradient and the solute concentration gradient were applied to the annular pool. The capillary ratio was assumed to be −1, which means that the solutal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The enhanced buoyancy-driven flow, due to the nonuniform solute concentration distribution in the axial direction, carries a lot of Ge 1-x Si x melt from the crucible bottom to the free surface, close to the sidewall at a large thermal capillary Reynolds number. Thus, the oscillatory spoke pattern swings in the azimuthal direction and merges, which is reported in Reference [24]. On the other hand, the amplitude of the surface solute concentration fluctuation decreases slightly, because of the increase of the wave number.…”
Section: Characteristics Of the 3d Oscillatory Flowsupporting
confidence: 59%
See 1 more Smart Citation
“…The enhanced buoyancy-driven flow, due to the nonuniform solute concentration distribution in the axial direction, carries a lot of Ge 1-x Si x melt from the crucible bottom to the free surface, close to the sidewall at a large thermal capillary Reynolds number. Thus, the oscillatory spoke pattern swings in the azimuthal direction and merges, which is reported in Reference [24]. On the other hand, the amplitude of the surface solute concentration fluctuation decreases slightly, because of the increase of the wave number.…”
Section: Characteristics Of the 3d Oscillatory Flowsupporting
confidence: 59%
“…Figure 3 gives the variations of critical thermal capillary Reynolds numbers along the crystal or crucible rotation Reynolds number. This dichotomy is successfully applied for obtaining the critical thermal capillary Reynolds numbers [24,25], and maximum deviation is controlled below 100. The critical thermal capillary Reynolds number at a non-rotation Cz configuration is 4.1 × 10 3 , which is much larger than that of pure fluids [9,10].…”
Section: Critical Conditions For the Flow Destabilizationmentioning
confidence: 99%
“…They reported three different oscillatory modes and found that the onset of instability correlates with a supercritical Hopf bifurcation. Later, Yu et al [23] and Chen et al [24,25] have performed simulations on the flow pattern transitions of binary mixture with a -1 capillary ratio in an annular pool, which is a simplified model for Cz configuration. Various types of flow patterns were observed with the increase of the thermocapillary Reynolds number, such as concentric rolls, petal-like, spokes, rosebud-like patterns and vibrating spoke patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Transient intermittency in the supercritical branch is observed and physical instability mechanisms of the subcritical branch are identified. Yu et al [8] reported a counter-intuitive transition route from a perspective of the flow field in the capillary flow. They considered that the reverse transition from the three-dimensional unsteady flow to the steady flow is the reason that the spatial complexity of the flow increases as the thermal Marangoni number increases.…”
Section: Introductionmentioning
confidence: 99%